An exegesis of the parable of the Good Samaritan (Lk 10:25–35) and its relevance to the challenges caused by COVID-19 - Chamburuka, Philemon M. (HTS teologiese studies, 2020)
The article is on the exegesis of the parable of the Good Samaritan (Lk 10:25–35) and its relevance to the challenges that are being posed by COVID-19. Through the historical-critical approach, the article has concluded that the parable is relevant in troubleshooting the challenges that are caused by COVID-19, such as discrimination, stigma, hate and stereotypes. The article sees COVID-19 as teaching humanity the important lesson that no one can live in isolation, however powerful or economically strong they are. Therefore, there is a need to take the opportunity of being a neighbour. Neighbourhood is understood as offering services to those in need and COVID-19 has presented a chance to the entire world to help someone with needs. A need-based world requires neighbours and this makes the parable relevant.Contribution: This article is a reflection of the challenges that are currently faced by people in response to the COVID-19 pandemic. It is within the scope of this theological journal that issues of identity, relationships, and theological reflection should be addressed, hence the article fits well within this scope.